2019
DOI: 10.1098/rsbl.2018.0909
|View full text |Cite
|
Sign up to set email alerts
|

Homophily around specialized foraging underlies dolphin social preferences

Abstract: Individuals often associate socially with those who behave the same way. This principle, homophily, could structure populations into distinct social groups. We tested this hypothesis in a bottlenose dolphin population that appeared to be clustered around a specialized foraging tactic involving cooperation with net-casting fishermen, but in which other potential drivers of such social structure have never been assessed. We measured and controlled for the contribution of sex, age, genetic relatedness, home range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…For example, populations of bottlenose dolphins Tursiops sp . are often divided into social communities assorted by learnt foraging tactics (Machado et al., 2019; Mann, Stanton, Patterson, Bienenstock, & Singh, 2012; Wild et al., 2019), illustrating the idea that the more individuals interact, the more opportunities they have for copying each other, thus highlighting how social decisions can reinforce behavioural homogeny. Models have shown that the feedback between information transmission and social decision‐making can stimulate the formation of stable groups within otherwise unstructured, well‐mixed, populations with (Cantor et al., 2015) and without any complex decision‐making (Cantor & Farine, 2018).…”
Section: From Individuals To Societies and Back: Two Established Feedmentioning
confidence: 99%
“…For example, populations of bottlenose dolphins Tursiops sp . are often divided into social communities assorted by learnt foraging tactics (Machado et al., 2019; Mann, Stanton, Patterson, Bienenstock, & Singh, 2012; Wild et al., 2019), illustrating the idea that the more individuals interact, the more opportunities they have for copying each other, thus highlighting how social decisions can reinforce behavioural homogeny. Models have shown that the feedback between information transmission and social decision‐making can stimulate the formation of stable groups within otherwise unstructured, well‐mixed, populations with (Cantor et al., 2015) and without any complex decision‐making (Cantor & Farine, 2018).…”
Section: From Individuals To Societies and Back: Two Established Feedmentioning
confidence: 99%
“…Information state can also determine the maintenance of social bonds-having similar social traits can facilitate cohesion among individuals by allowing them to synchronise and coordinate their activities(Coussi-Korbel & Fragaszy 1995). For example, populations of bottlenose dolphins are often divided into social communities assorted by learnt foraging tactics(Mann et al 2012;Machado et al 2019;Wild et al 2019), illustrating the idea that the more individuals interact, the more opportunities they have for copying each other, thus highlighting how social decisions can reinforce behavioural homogeny. Models have shown that the feedback between information transmission and social decision-making can stimulate the formation of stable groups within otherwise unstructured, well-mixed, populations with(Cantor et al 2015) and without any complex decision-making(Cantor & Farine 2018).…”
mentioning
confidence: 99%
“…Taking into account the confounding effects of 5 structural variables (spatial and temporal overlap, gregariousness, size and sex), which are known to influence association patterns (e.g. Godde et al 2013; Diaz-Aguirre et al 2019; Machado et al 2019; Perryman et al 2019), we found that blacktip reef sharks in Moorea had structured associations and affiliations, although most of the network structure was driven by spatiotemporal overlap. However, social proximity was not predicted by the genetic relatedness between sharks both at the association, affiliation and community levels.…”
Section: Discussionmentioning
confidence: 92%